2015
DOI: 10.1016/j.hcl.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Complications of Distal Radius Fractures

Abstract: Synopsis Treating a fracture of the distal radius may require the surgeon to make a difficult decision between surgical treatment and nonsurgical management. The use of surgical fixation has recently increased owing to complications associated with conservative treatment. However, conservative action may be necessary depending on certain patient factors. The treating surgeon must be aware of the possible complications associated with distal radius fracture treatments to prevent their occurrence. Prevention can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 78 publications
2
67
1
7
Order By: Relevance
“…In the present study, 4 types of double-column die-punch fracture of the distal radius were included as follows: A comprehensive fracture classification system must include all fracture types and reflect the characteristics of the fractures. In addition, the system must exhibit an optimal performance (19,23,24). In the present study, all of the 498 patients were successfully grouped in the absence of missing data.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the present study, 4 types of double-column die-punch fracture of the distal radius were included as follows: A comprehensive fracture classification system must include all fracture types and reflect the characteristics of the fractures. In addition, the system must exhibit an optimal performance (19,23,24). In the present study, all of the 498 patients were successfully grouped in the absence of missing data.…”
Section: Discussionmentioning
confidence: 94%
“…The results indicated that the Three-Column Classification system The Melone classification II and Fernandez classification III are established classifications of die-punch fractures, which were denoted as type III fractures in the present study (15,16). The Melone and Fernandez classification systems have been extensively cited by previous studies (17)(18)(19)(20)(21). Although this type of double-column die-punch fracture is widely known, the description of double-column die-punch fractures of the distal radius has not been previously reported (10,22).…”
Section: Discussionmentioning
confidence: 98%
“…6,32 Currently, volar placement of a plate is favored widely. 6,9 In the current study, a buttress plate is placed volarly and no impingement is worried.…”
Section: Discussionmentioning
confidence: 99%
“…Las complicaciones de las fracturas del radio distal son frecuentes (21-27%), pueden ocurrir tanto con el tratamiento conservador como con el quirúrgico y tienen diversas causas: la pérdida de movimiento está asociada a deformidad marcada, decremento de los arcos de movilidad articular, artrofibrosis, isquemia de Volkmann, contracturas y rigidez en los dedos; la mal unión y la unión retardada ocurren cuando la fractura sana con alineación inadecuada, incongruencia articular, longitud incorrecta o la combinación de todas las anteriores; la neuritis, la comprensión del nervio y el síndrome doloroso regional complejo se relacionan con una alta severidad en la fractura; las tenosinovitis, laceraciones y rupturas tendinosas dependen del tratamiento quirúrgico, y las infecciones de tejidos blandos y osteomielitis se asocian a fracturas abiertas o al material de osteosíntesis. Complicaciones menos frecuentes implican cicatrización queloide, artritis, artrosis, entre otras [12][13] .…”
Section: Introductionunclassified